Postoperative pain outcomes following uniportal vs. multiportal video-assisted thoracoscopic surgery: a systematic review and meta-analysis - Kanani, Fahim; Zahalka, Alaa; Kamar, Moshe; Nugzar, Rijini; Wiesel, Ory; Refaely, Yael; Salhab, Anas; Shimonov, Mordechai; Gonzalez-Rivas, Diego; Abu Akar, Firas (Frontiers in Surgery, 2025)
BackgroundVideo-assisted thoracoscopic surgery (VATS) has evolved from multiportal to uniportal approaches, theoretically offering reduced postoperative pain through single intercostal space access. However, inconsistent surgical definitions and mixed evidence have limited clinical guidance.ObjectivesTo systematically evaluate postoperative pain outcomes between true uniportal VATS (strictly defined by the 2019 European Society of Thoracic Surgeons criteria) and multiportal VATS for lung resections.MethodsWe searched five databases during the period between January 2000 and January 2025 for comparative studies of uniportal vs. multiportal VATS reporting pain outcomes. True uniportal VATS requires a single intercostal incision (2.5–5 cm) with all instruments through one port. Meta-analyses were excluded to prevent data duplication. The primary outcome was 24-h pain intensity. A random-effects meta-analysis was performed to calculate standardized mean differences (SMD) with 95% confidence intervals (CI). Risk of bias was assessed using the revised Cochrane risk-of-bias tool (ROB 2) randomized controlled trials (RCTs) and the risk-of-bias in non-randomized studies of interventions (ROBINS-I) for observational studies.ResultsNineteen studies (6 RCTs, 13 observational) comprising 2,544 patients (1,156 uniportal, 1,388 multiportal) met the inclusion criteria. Uniportal VATS significantly reduced pain at 24 h (SMD −0.98, 95% CI −1.12 to −0.84, p < 0.0001), equating to a reduction of 2.5 points on a 10-point scale. Benefits persisted at 48 h (SMD −0.80) and 7 days (SMD −0.58). Opioid consumption decreased by 10.6 mg of morphine equivalents (95% CI −14.8 to −6.4). Heterogeneity was moderate (I2 = 63.6%). Studies using standardized analgesia protocols showed larger effects (SMD −1.05) with lower heterogeneity (I2 = 58.4%). Meta-regression identified a decrease in effect sizes over time (β = 0.05 per year, p = 0.024). Sensitivity analyses confirmed the robustness of the results, with all iterations maintaining statistical significance.ConclusionsTrue uniportal VATS provides clinically meaningful reductions in postoperative pain compared with multiportal approaches when applying strict anatomical criteria. Benefits are enhanced with standardized perioperative analgesia protocols. Implementation should consider local expertise and the observed heterogeneity in treatment effects.RegistrationNot prospectively registered; PRISMA 2020 guidelines followed.